Sulphate sorption at high equilibrium concentration in Andosols - Delfosse, Thomas; Delmelle, Pierre; Delvaux, Bruno (Geoderma, 2006)
The main process by which inorganic SO 4 2− inputs are retained in soils is through adsorption on soil colloids. However, in soils subject to intense SO 4 2− addition, precipitation of Al x (SO 4) y (OH) z minerals also may contribute to SO 4 2− sorption. While direct observation of Al x (SO 4) y (OH) z precipitate in soil has been reported only recently, SO 4 2− sorption isotherms experiments have been rarely performed to distinguish between adsorption and precipitation processes. Traditionally, SO 4 2− sorption experiments have involved relatively low SO 4 2− concentrations in the range 0–5 mM. However, for SO 4 2− precipitation to occur, higher concentrations may be needed. Here, we evaluated SO 4 2− sorption in four contrasting Andosols samples by measuring sorption isotherms with SO 4 2− concentrations ranging from 0.1 to 15 mM and under low pH conditions (pH 4). A 1 h sorption equilibration time was allowed. All sorption isotherms showed a distinct biphasic shape. In the lowest SO 4 2− concentration range (< 5 mM), SO 4 2− sorption obeyed a Langumir isotherm, whereas at higher SO 4 2− concentrations (> 6 mM), SO 4 2− sorption could be described by a linear isotherm. The transition between a Langmuir-type and a linear-type isotherm also corresponded to the transition point where the solution was oversaturated with respect to Al x (OH) y (SO 4) z minerals, according to thermodynamic calculations. We interpreted these results in terms of initial SO 4 2− adsorption onto the surface of soil constituents at lower dissolved SO 4 2− concentrations followed by SO 4 2− precipitation at high dissolved SO 4 2− concentrations.